Characterisation of novel mitochondrial proteins in Trypanosoma brucei - Rašková, Vendula (Jihočeská univerzita, 2023)
This study analyses and characterises novel mitochondrial proteins in the parasitic protist Trypanosoma brucei. Applying phylogenetic analysis was described the evolutionary origin of ZapE protein in eukaryotes, using a newly developed proximity-dependent biotinylation approach (BioID2) we identified ZapE interaction partners like Oxa1. We also discovered a relationship when distribution of mitochondrial ZapE is restricted only to organisms with Oxa1, respiratory complexes, and a mitochondrial genome. TbPams were detected by phylogenetic analyses as orthologs of corresponding proteins in Opistokonts. We analyse the function of TbPam18 and TbPam16 in the replication of the mitochondrial DNA and determine, how the TMDs of TbPam18 and TbPam16 are essential for their functions. Finally, we evaluated a set of putative mitochondrial proteins of the heterolobosean N. gruberi defined by Localisation of Organelle Proteins by Isotope Tagging (LOPIT) and analyse the origin of mtFfh and mtFtsY.
Characterisation of novel mitochondrial proteins in Trypanosoma brucei
Keywords: Trypanosoma brucei; kDNA; mitochondrion; TbPam protein; ZapE; kinetoplast; Trypanosoma brucei; kDNA; mitochondrion; TbPam protein; ZapE; kinetoplast